2004
DOI: 10.1093/cercor/bhh198
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Real and Imagined Sensorimotor Coordination

Abstract: Much debate in the behavioral literature focuses on the relative contribution of motor and perceptual processes in mediating coordinative stability. To a large degree, such debate has proceeded independently of what is going on in the brain. Here, using blood oxygen level-dependent measures of neural activation, we compare physically executed and imagined rhythmic coordination in order to better assess the relative contribution of hypothesized neuromusculoskeletal mechanisms in modulating behavioral stability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 67 publications
7
53
0
7
Order By: Relevance
“…The present results complement and extend previous findings showing that effects of neuronal cross-talk during programming of bimanual movements are apparent in motor imagery (Heuer et al, 1998). In addition, they go in line with neurological findings showing that stimulus and coordination constraints influence imagination and execution in a similar way (Oullier et al, 2005). If task performance had been limited by biomechanical or motor constraints, slower parallel than symmetric movements should have been observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results complement and extend previous findings showing that effects of neuronal cross-talk during programming of bimanual movements are apparent in motor imagery (Heuer et al, 1998). In addition, they go in line with neurological findings showing that stimulus and coordination constraints influence imagination and execution in a similar way (Oullier et al, 2005). If task performance had been limited by biomechanical or motor constraints, slower parallel than symmetric movements should have been observed.…”
Section: Discussionsupporting
confidence: 92%
“…First, our results and previous results (Heuer et al, 1998;Oullier et al, 2005) suggest that different types of coordination constraints are present in imagery. Thus, it should be possible to effectively apply mental practice to activities which require a high amount of coordination between different limbs, like rowing.…”
Section: Discussionsupporting
confidence: 74%
“…This notion is bolstered by evidence showing that observation of another person performing rhythmic movements generates a kinematically specific memory trace of the observed motions in primary motor cortex (Stefan, Cohen, Duque, Mazzocchio, Celnik, Sawaki, Ungerleider, & Classen, 2005). Moreover, representations at the neural level have been shown to be highly flexible and context-dependent (Jantzen, Steinberg, & Kelso, 2004;, influenced both by environmental (Wheeler, Peterson & Buckner, 2000) and task demands (Oullier, Jantzen, Steinberg, & Kelso, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Work employing fMRI has shown that rhythm perception recruits brain areas that are traditionally considered to be part of the motor system. Thus, areas involved in motor control and learning, action selection, planning, and sequencing are activated in tasks that require beat finding, imagined sensorimotor synchronization, and recognition memory for rhythm patterns (Grahn, 2009;Janata & Grafton, 2003;Oullier, Jantzen, Steinberg, & Kelso, 2005;Zatorre, Chen, & Penhune, 2007). One possibility, then, is that rhythm perception involves the simulation of action.…”
Section: Perception As Covert Actionmentioning
confidence: 99%